The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.addbeh.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of nicotine deprivation and indices of alcohol use behavior to implicit alcohol and cigarette approach cognitions in smokers

Abstract: Alcohol and smoking frequently co-occur and alcohol is a primary trigger for smoking behavior and relapse back to smoking. This study examined whether several indices of alcohol use behavior and consequences of use would be associated with changes in implicit alcohol-approach versus implicit cigarette-approach cognitions under cigarette deprived and non-deprived cognitions in a 109 smokers who drank at risky or non-risky levels. An Implicit Association Task (IAT) measured how quickly respondents paired alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Previous research from different fields has been trying to link implicit and explicit attitudes to actual behavior (43)(44)(45), with moderate success. Until today, it seems difficult to explain the gap between people's attitudes and actual behavior (46).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research from different fields has been trying to link implicit and explicit attitudes to actual behavior (43)(44)(45), with moderate success. Until today, it seems difficult to explain the gap between people's attitudes and actual behavior (46).…”
Section: Discussionmentioning
confidence: 99%
“…[32, 54, 55•]), but importantly these were the studies that did not observe an approach bias for the disorder-related substance. Finally, the experimental studies highlighted a number of moderators that strengthened approach bias and its relationship with consumption behaviour, such as relevant task instructions [48, 80••], negative or positive affect [64,65,66••], low cognitive load [68], hunger [78] and withdrawal from other substances [71]. Together, these findings support the main premises of dual-process models of behaviour, namely, that automatically activated tendencies predict behaviour when the reflective system is relatively weak (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge for the understanding of automatically activated approach-avoidance tendencies is co-morbidity. Indeed, research examined in this review highlighted that tobacco and alcohol use were interrelated [35,71]. Thus, another direction for future research is the concurrent assessment of approach-avoidance biases and related behaviours for multiple substances.…”
Section: Implications For Future Researchmentioning
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, this is the only study that has examined the effects of prolonged nicotine reduction (i.e., 6 weeks) on alcohol drinking. Past studies of acute nicotine deprivation or abstinence have reported inconsistent effects on alcohol craving and drinking behavior (Cooney et al, 2003, Colby et al, 2004, Cohn et al, 2017, Palfai et al, 2000), but these studies may not closely model what is expected to occur in the marketplace as a result of new FDA product standards – a gradual reduction in nicotine content in cigarettes. As we anticipate changes in nicotine content in cigarettes, it is now time to reflect on how alcohol-focused researchers, clinicians, and policy makers, who have had a long-standing focus on harm reduction, can prepare for upcoming changes in the nicotine-focused harm reduction regulatory framework for tobacco.…”
mentioning
confidence: 99%